Rancang Bangun Pembuatan Sitem Informasi Manajemen Dokumen E-Arsip PT.PLN (Persero) Unit Induk Pembangkitan Sumatera Bagian Selatan - Wijaya, Indra Dharma; Irawan, Edi; Rahmanto, Anugrah Nur (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
This study aims to design a document management application called Electronic Archive Information System (E-Arsip) for PT.PLN (Persero) Unit Induk Pembangkitan Sumatera Bagian Selatan in the field of general and communication. Currently, the company still utilizes a conventional filing system by storing invoice documents from outsourcing companies collaborating with PT.PLN (Persero) UIKSBS on archive shelves, with data summaries recorded in an agenda book. The limitations of this conventional filing system lead to difficulties in retrieving the required archival documents due to the increasing number of stored documents in the archive shelves. Additionally, there are frequent errors in data entry for the searched letters, making it challenging to locate the data. To address these issues, this research focuses on designing the E-Arsip application to assist the secretarial staff (PIC) of PT.PLN (Persero) UIKSBS in managing incoming and outgoing letter archives. The application will implement the Levenshtein String algorithm to handle data entry errors encountered during system searches. The outcome of this research is a modern web-based application design for managing incoming and outgoing document archives. Furthermore, the use of the Levenshtein String algorithm will help display the intended data in case of typographical errors during data search. By implementing the E-Arsip application, it is expected that PT.PLN (Persero) UIKSBS can enhance efficiency in letter archive management, reduce data search errors, and modernize the overall filing system.